Global gender constitutionalism and women's citizenship : a struggle for transformative inclusion / Ruth Rubio-Marin, Universidad de Sevilla. - Rubio-Marín, Ruth (Cambridge studies in constitutional law., 2022)
Constitutions around the world have overwhelmingly been the creation of men, but this book asks how far constitutions have affirmed the equal citizenship status of women or failed to do so. Using a wealth of examples from around the world, Ruth Rubio-Marín considers constitutionalism from its inception to the present day and places current debates in their vital historical context. Rubio-Marín adopts an inclusive concept of gender and sexuality, and discusses the constitutional gender order as it has been shaped by debates such those around same-sex marriage and the rights of trans persons. Covering a wide range of themes, from reproductive rights to political gender quotas and violence against women, this book offers a comprehensive feminist account of constitutional law. Truly international in scope and ambitious in subject matter, this is an invaluable resource for students and scholars working on gender within multiple disciplines.